Human rights awareness education to prevent bullying behavior at school - Hariyanti Hariyanti; Gigieh Cahya Permady; Anif Istianah; Saepudin Kartasasmita (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
The prevalence of bullying, a serious issue in primary and secondary schools, underscores the need for effective prevention strategies. This study aims to develop a human rights education model to address this concern. The primary objective is to design a comprehensive human rights education model tailored for school environments. This model aims to prevent bullying behavior by fostering a culture of respect and empathy among students. A literature review methodology was employed to analyze existing problems related to bullying and identify potential solutions. Theoretical frameworks and empirical research findings were utilized to develop the proposed human rights education model. The results of this research suggest the development of prevention strategies and the creation of a pocketbook containing human rights education materials accessible to students. Additionally, it suggests the use of engaging learning media to facilitate a better understanding of human rights concepts, which are often abstract and challenging to grasp through traditional teaching methods. The human rights education model presented in this study is adaptable for both primary and secondary education. It emphasizes the importance of early intervention to prevent bullying from becoming entrenched in school cultures. By targeting students' moral and cognitive development, this model aims to break the cycle of victimhood and aggression associated with bullying. This study contributes to the field of education by proposing a practical and holistic approach to addressing bullying in schools. The proposed human rights education model provides educators with a framework to promote a safe and inclusive learning environment